Scaling Geological Fracture Network from a Micro to a Macro Scale - Rouhollah Basirat; Kamran Goshtasbi; Morteza Ahmadi (Fracture and Structural Integrity)
Characterizing fracture systems at various scales, modeling fracture distributions, and clarifying scale relations that correlate total fracture systems are of paramount importance in geology, mining, civil engineering, and petroleum engineering. In this paper, the conditions of fracture network geometry are investigated in a field scale (about 100 m) and a core sample scale (several centimeters). To achieve this purpose, field surveys and coring of rock outcrops were performed in the Asmari Formation of Iran. Fractures were manually sampled from rock outcrops on the field scale while micro-fractures were surveyed using CT-scan images of core samples on a small scale. To compare the fracture network geometry, two perspectives of fractal dimensions and orientation of fractures were used. The results showed that the fractal dimension has the same value in both field and core scales and the orientation of the fractures is similar in both scales. Therefore, it can be claimed that in the Asmari Formation of Iran the structure of the fracture network is similar in two studied scales.